SELF-DEVELOPMENT EDUCATION IN IMPROVING THE ENTREPRENEURIAL SPIRIT OF STUDENTS THROUGH THE EMPOWERMENT OF COOPERATIVES OF TAHFIDZUL QURâ€™AN NURUDDIN SALAM ISLAMIC BOARDING SCHOOL IN SAMARINDA CITY - Rabiatul Adawiyah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community development activity is expected that the participants have knowledge and insight into entrepreneurship which includes growing into a creative person who can create from non-existent to existing, growing into a productive and non-consumptive person, and willing to try to become an entrepreneur to train independence, relying on their creativity. The implementation of this community service was carried out at the Tahfidzul Quran Nuruddin Salam Islamic Boarding School. This activity is in the form of practice and cultivation of entrepreneurial spirit at the Al-Hasyir Cooperative, Tahfidzul Quran Nuruddin Salam Islamic Boarding School. The shaper of the entrepreneurial spirit at the Tahfidzul Quran Nuruddin Salam Islamic boarding school has proceeded in accordance with the creative process and the incarnation of intuition, imagination, ideas, ideas, and the existence of resources to be processed to achieve the planned goals. It assumes the absence of uniformity in both technical and theoretical aspects that inspired it. The method of Islamic boarding schools in developing the entrepreneurial spirit of Tahfidzul Quran Nuruddin Salam students has been carried out by prioritizing the spirit of students who have charitable character and become independent individuals in facing changes in an increasingly advanced world, so that later there will be created human students who are able to manage the economy and are ready to color the world with Islamic entrepreneurial provisions, because Islam has made the search for treasure as one of the tools of worship and approachÂ  self to Allah Almighty